Water stress combined with sulfur deficiency in pea affects yield components but mitigates the effect of deficiency on seed globulin composition. (11th March 2019) - Henriet, Charlotte; Aimé, Delphine; Térézol, Morgane; Kilandamoko, Anderson; Rossin, Nadia; Combes-Soia, Lucie; Labas, Valerie; Serre, Rémy-Félix; Prudent, Marion; Kreplak, Jonathan; Vernoud, Vanessa; Gallardo, Karine
Abstract: Water stress and sulfur (S) deficiency are two constraints increasingly faced by crops due to climate change and low-input agricultural practices. To investigate their interaction in the grain legume pea ( Pisum sativum ), sulfate was depleted at the mid-vegetative stage and a moderate 9-d water stress period was imposed during the early reproductive phase. The combination of the stresses impeded reproductive processes in a synergistic manner, reducing seed weight and seed number, and inducing seed abortion, which highlighted the paramount importance of sulfur for maintaining seed yield components under water stress. On the other hand, the moderate water stress mitigated the negative effect of sulfur deficiency on the accumulation of S-rich globulins (11S) in seeds, probably due to a lower seed sink strength for nitrogen, enabling a readjustment of the ratio of S-poor (7S) to 11S globulins. Transcriptome analysis of developing seeds at the end of the combined stress period indicated that similar biological processes were regulated in response to sulfur deficiency and to the combined stress, but that the extent of the transcriptional regulation was greater under sulfur deficiency. Seeds from plants subjected to the combined stresses showed a specific up-regulation of a set of transcription factor and SUMO ligase genes, indicating the establishment of unique regulatory processes when sulfur deficiency is combined with water stress. Abstract : Moderate water stress combined with sulfur deficiency during seed development in pea synergistically affects reproductive processes, but mitigates the negative impact of the deficiency on the seed transcriptome and rebalances seed globulin composition.